PENILAIAN KINERJA GURU (PKG) DALAM MENINGKATKAN MUTU GURU - Permana, Aji (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
Teacher performance assessment is a assessment of tasks and functions related to carried out in accordance with applicable regulations in order to ensure the learning process at all levels of education. This research is a qualitative method with reference to problem solving strategies. the aim of improving teacher quality in the learning process. The research subjects were teachers of SMAN 1 Karangnunggal with a total of 36 people. results Based on the research 4 teacher competencies are already high and there is an increase from the previous year. For pedagogic ability, the average obtained is 89,42% and is included in the high category. Professional personality obtained on average is 92,3% and is included in the high category. Social Competence, Social competence obtained an average of 91,7% and included in the high category. Professional competence obtained on average is 94,4% and is included in the high category. This shows that the quality of teacher quality is increasing